Distribution of Chlamydia trachomatis ompA genotypes and its association with abnormal cervical cytology among women of reproductive age in Shenzhen, China - Lan-lan Liu; Si Sun; Li Zhang; Qiu-hong Wu; Li-shan Tian; Bo Li; Xiang-sheng Chen; Zhen-zhou Luo (Frontiers in Public Health, 2022)
BackgroundMany studies have focused on the distribution and specific clinical symptoms caused by Chlamydia trachomatis. Still, relatively few studies have focused on the associations between Chlamydia trachomatis genotypes and cervical intraepithelial lesions.ObjectivesThis study was conducted to determine the distribution of Chlamydia trachomatis genotypes and its associations with cervical intraepithelial lesions among women of reproductive age. The presence of other STIs coinfection was also evaluated.Method375 Chlamydia trachomatis positive cervical swabs collected from women of reproductive age were analyzed though molecular assay. Multivariate logistic regression analyses (covariates include contraception, gravidity (≥1), abnormal vaginal discharge, adverse pregnancy outcomes, reproductive tract symptoms and abnormal cervical cytology) were performed to evaluate the associations between Chlamydia trachomatis genotypes and cervical intraepithelial lesions and genital clinical symptoms.ResultsAmong 375 Chlamydia trachomatis positive cervical swabs, the prevalence of coinfection with Neisseria gonorrhoeae, Candida albicans, Trichomonas vaginitis, Vulvovaginal candidiasis, and HPV were 0.8%, 2.7%, 2.4%, 10.1% and 15.5%, respectively. 306 were genotyped successfully, and nine genotypes were identified. The most common genovar was E (25.16%, 77/306), followed by J (22.55%, 69/306), F (17%, 52/306), D (14.4%, 44/306), K (7.2%, 22/306), G (6.9%, 21/306), H (5.2%, 16/306), B (1.0%, 3/306), Ia (0.7%, 2/306). Genotype H was associated with abnormal cervical cytology [p = 0.006, aOR = 8.16 (1.86–36.6)]. However, this study observed no association between Chlamydia trachomatis genotypes and any genital clinical symptoms.ConclusionsChlamydia trachomatis genotype H may be a high risk factor for cervical intraepithelial lesions, which is useful for treatment and management measures for patients with cervical intraepithelial lesions.